APPLICATION OF DIFFERENT FEED AND FEEDING PERIODS DURING REARING OF MALAY COMBTAIL (Belontia hasselti) LARVAE - Yonarta, Danang; Tanbiyaskur, Tanbiyaskur; Weda, I Gede Arya; Gustiar, Fitra (Politeknik Kelautan dan Perikanan Jembrana, 2024)
Feed type and feeding period play critical roles in growth and survival of fish larvae during rearing period, for which no related studies are available for Malay combtail larvae. This research aimed to determine the best feed type and feeding period for growth and survival of Malay combtail larvae. The research experiment was arranged in a completely randomized design with five treatments of different feed and feeding periods with three replications, namely (P1) nauplii Artemia sp. (4-15 days), Moina sp. (14-24 days), and Tubifex sp. (23-35 days), (P2) nauplii Artemia sp. (4-13 days), Moina sp. (12-20 days), and Tubifex sp. (19-35 days), (P3) nauplii Artemia sp. (4-11 days), Moina sp. (10-16 days), and Tubifex sp. (15-35 days), (P4) nauplii Artemia sp. (4-11 days), Moina sp. (12-20 days), and artificial feed (19-35 days), and (P5) nauplii Artemia sp. (4-11 days), Moina sp. (10-16 days), and artificial feed (15-35 days). The results showed that P4 was the best treatment, where larvae had better absolute growth in length and weight and survival of 11.09 ± 0.03 mm, 0.083 ± 0.001 g, and 50.67 ± 1.15%, respectively. Variations of water quality parameters during the experiment in all treatments ranged between 6.0-6.6 for pH, 0.017-0.091 mg L-1 for ammonia, and 4.03-4.43 mg L-1 for dissolved oxygen. The results of this research that the sequential and early application of live feed and much later artificial feed appication in combination with the timely feeding period and the larval development improve growth and survival of Malay combtail larvae.Jenis pakan dan periode pemberian pakan memainkan peran penting dalam pertumbuhan dan kelangsungan hidup larva ikan selama masa pemeliharaan, hingga saat ini belum ada penelitian terkait mengenai larva ikan selincah. Penelitian ini bertujuan untuk mengetahui jenis pakan dan lama pemberian pakan yang terbaik untuk pertumbuhan dan kelangsungan hidup larva ikan selincah. Penelitian disusun dalam rancangan acak lengkap dengan lima perlakuan pakan dan lama pemberian pakan berbeda dengan tiga ulangan yaitu (P1) nauplii Artemia sp. (4-15 hari), Moina sp. (14-24 hari), dan Tubifex sp. (23-35 hari), (P2) nauplii Artemia sp. (4-13 hari), Moina sp. (12-20 hari), dan Tubifex sp. (19-35 hari), (P3) nauplii Artemia sp. (4-11 hari), Moina sp. (10-16 hari), dan Tubifex sp. (15-35 hari), (P4) nauplii Artemia sp. (4-11 hari), Moina sp. (12-20 hari), dan pakan buatan (19-35 hari), dan (P5) nauplii Artemia sp. (4-11 hari), Moina sp. (10-16 hari), dan pakan buatan (15-35 hari). Hasil penelitian menunjukkan bahwa P4 merupakan perlakuan terbaik, di mana larva mempunyai pertumbuhan panjang dan berat absolut yang lebih baik serta kelangsungan hidup masing-masing sebesar 11,09 ± 0,03 mm, 0,083 ± 0,001 g, dan 50,67 ± 1,15%. Variasi parameter kualitas air selama percobaan pada semua perlakuan berkisar antara 6,0-6,6 untuk pH, 0,017-0,091 mg L-1 untuk amoniak, dan 4,03-4,43 mg L-1 untuk oksigen terlarut. Hasil dari penelitian ini adalah pemberian pakan hidup secara berurutan dan dini serta pemberian pakan buatan yang dikombinasikan dengan periode pemberian pakan yang tepat waktu dan perkembangan larva akan meningkatkan pertumbuhan dan kelangsungan hidup larva ikan selincah.